Intrinsically Disordered Tardigrade Proteins Self‐Assemble into Fibrous Gels in Response to Environmental Stress. (25th November 2021) - Malki, Anas; Teulon, Jean‐Marie; Camacho‐Zarco, Aldo R.; Chen, Shu‐wen W.; Adamski, Wiktor; Maurin, Damien; Salvi, Nicola; Pellequer, Jean‐Luc; Blackledge, Martin
Abstract: Tardigrades are remarkable for their ability to survive harsh stress conditions as diverse as extreme temperature and desiccation. The molecular mechanisms that confer this unusual resistance to physical stress remain unknown. Recently, tardigrade‐unique intrinsically disordered proteins have been shown to play an essential role in tardigrade anhydrobiosis. Here, we characterize the conformational and physical behaviour of CAHS‐8 from Hypsibius exemplaris. NMR spectroscopy reveals that the protein comprises an extended central helical domain flanked by disordered termini. Upon concentration, the protein is shown to successively form oligomers, long fibres, and finally gels constituted of fibres in a strongly temperature‐dependent manner. The helical domain forms the core of the fibrillar structure, with the disordered termini remaining highly dynamic within the gel. Soluble proteins can be encapsulated within cavities in the gel, maintaining their functional form. The ability to reversibly form fibrous gels may be associated with the enhanced protective properties of these proteins. Abstract : The conformational behaviour of an intrinsically disordered protein responsible for protecting tardigrades against extreme stress has been characterized. The protein assembles into fibres and fibrillar gels as a function of temperature and concentration. The disordered tails remain flexible within the gel cavities, which can encapsulate client proteins in their native state.